Clinical profile of cervical lymphadenopathy and to find diagnostic efficacy of fine-needle aspiration cytology, ultrasonography and histopathological examination - Sharma, Nitin; Singh, Maya; Sharma, Pritosh; Nahar, Rahul; Goyal, V. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Cervical lymphadenopathy is the sign of a disease process which involves lymph nodes that are anomalous in uniformity and dimensions. It is very vital to exercise fine-needle aspiration biopsy, histopathological investigation, and ultrasonography for the diagnosis of palpable lesions. Methods: This is a prospective study of 12-month duration from January 2018 to December 2018 in 61 patients presenting with cervical lymphadenopathy admitted in the ENT Department at Geetanjali Medical College and Hospital, Udaipur. Results: In biopsy, most common diagnosis was chronic granulomatous lymphadenitis i.e. in 62.3% of the patients. As compared to biopsy, fine-needle aspiration cytology (FNAC) showed chronic granulomatous lymphadenitis in 46% of the patients, with overall sensitivity of 91.1%, and specificity of 60.0%. and accuracy of 88.5%. Whereas ultrasonography (USG) reported, 64% cervical lymphadenopathy in patients, with overall sensitivity came out to be 91.1%, specificity to be 40.0%, accuracy was 86.9%. Conclusions: Present study showed that biopsy is the gold standard procedure for diagnosis of cervical lymphadenopathy lesions followed by FNAC, USG. Tuberculous lymphadenitis was most common diagnosis made by the diagnostic modalities.